Toughening of poly(lactide) using polyethylene glycol methyl ether acrylate: Reactive versus physical blending. Issue 6 (15th April 2015) - Kfoury, Georgio; Raquez, Jean‐Marie; Hassouna, Fatima; Leclère, Philippe; Toniazzo, Valérie; Ruch, David; Dubois, Philippe
<x xml:space="preserve">Abstract</x> To design high‐performance poly(lactide)‐based materials (PLA‐based) with improved toughness, two approaches based on the reactive extrusion (REx) process are investigated and compared in the present study. The first approach relies upon a two‐step procedure using a REx‐polymerized poly(ethylene glycol) methyl ether acrylate, i.e., poly(AcrylPEG), as a highly‐branched and compatible impact modifier for PLA. The free‐radical polymerization proves to be very efficient with a peroxide initiator concentration of 1 wt%. The as‐produced poly(AcrylPEG) is then melt‐blended with PLA by extrusion. The resulting materials exhibit largely increase impact resistance (ca. 35 kJ/m2) in presence of 20 wt% poly(AcrylPEG) in comparison with neat PLA (2.7 kJ/m2), while moderate ductility (tensile elongation at break <40%) and limited plasticization effect are observed. The second "one‐step" approach consists in in situ grafting of AcrylPEG onto PLA backbone via a one‐stage REx. The resulting materials exhibit substantially improved impact resistance (ca. 102 kJ/m2) for AcrylPEG loading of 20 wt%, high ductility (tensile elongation at break of ca. 150%) and efficient plasticization. A detailed characterization of the morphology of the materials has been performed using PF‐QNM‐AFM to better elucidate the structure‐property relationships. POLYM. ENG. SCI., 55:1408–1419, 2015. © 2015 Society of Plastics Engineers